An Evaluation of Differential Reinforcement in the Treatment of Pica. (3rd July 2020) - Muething, Colin; Call, Nathan A.; Clark, Seth
ABSTRACT: Common approaches to pica treatment involve intensive staffing and near continuous behavioral monitoring to proactively disrupt any attempts at this potentially life threatening behavior. Including differential reinforcement of discarding pica items as a contingency in such interventions has been suggested as a more practical treatment model, but the evidence base for this approach is limited. We replicated this work by evaluating differential reinforcement for discarding pica items in conjunction with response blocking and differential reinforcement of other behavior in the treatment of pica exhibited by two children. We extended this work by evaluating sustained reductions when therapist and caregiver monitoring was reduced.